Detailed micro-modeling approach and solution strategy for laterally loaded reinforced masonry shear walls. (15th December 2019) - Calderón, Sebastián; Arnau, Oriol; Sandoval, Cristián
Highlights: A detailed micro-modeling approach for simulating the lateral response of PG-RM shear walls is proposed. Numerical aspects such as integration order, iterative method or solver for linearized systems could have a strong influence on the model's response. Asymmetrical inverse-update iterative methods are suitable for solving models with asymmetrical stiffness matrixes. Using a non-parallel solver algorithm for solving equation systems of models with strong non-linear behavior could avoid obtaining different solutions for the same problems. Abstract: Although multiple experimental investigations have been performed to characterize the structural behavior of partially grouted reinforced masonry (PG-RM) shear walls, still many knowledge gaps exist due to the complexity of their mechanical behavior. Furthermore, the fact that PG-RM is a composite material has limited the progress of the numerical modeling of these elements. In order to contribute to the knowledge of the in-plane response of PG-RM walls, this paper presents a detailed micro-modeling approach to simulate the behavior of these walls under in-plane lateral loads. Numerical results are validated by comparison with experimental results of PG-RM walls with bed-joint reinforcement. Special attention is given to the numerical implementation and solution strategy of the models due to the difficulties of solving the strong nonlinearities involved in the walls' response. The obtained results allow us to conclude that the proposed approach is suitable for simulating the lateral response of PG-RM shear walls, including crack patterns observed during experimental tests. In addition, the performed parametric study shows that selecting adequate numerical parameters is vital to avoid misleading results.